STATE SUPPORT AND ITS IMPACT ON ECONOMIC GROWTH: THEORETICAL AND METHODOLOGICAL ASPECTS (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
The article comprehensively examines the state’s incentive policy and investment promotion mechanisms implemented since 2014 in the process of establishing and developing industrial zones in the Republic of Azerbaijan, focusing on their essence, objectives, and    outcomes. The study highlights the role of industrial zones in economic diversification, reducing regional development disparities, and ensuring sustainable growth in the non-oil sector. As a result of the analysis, existing forms of state support for industrial zones— including tax and customs incentives, infrastructure provision, financial mechanisms, and institutional assistance—were summarized, systematized, and classified. Various theoretical and methodological approaches to the concepts of state support, state support expenditures, investment incentives, and investment incentive expenditures were comparatively analyzed, revealing their economic essence, interrelations, and spheres of impact. The article conceptually and practically explores the mechanism through which state support influences economic growth, identifying both direct and indirect channels such as increased investment activity, industrial expansion, job creation, technological modernization, and productivity enhancement. A scientific  and methodological framework for evaluating the effectiveness of state support is proposed, along with measurable indicators and evaluation criteria. In addition, the structure, scope, and main sources of data required for empirical assessment—such as national statistical agencies, fiscal reports, and databases of industrial zone management bodies—are defined. The findings of the study hold significant scientific and practical value for improving industrial policy, ensuring efficient allocation of public resources, and maintaining sustainable economic growth.
Keywords: industrial zones, state support expenditures, investment incentive expenditures, economic growth.